2017
DOI: 10.18203/2394-6040.ijcmph20171339
|View full text |Cite
|
Sign up to set email alerts
|

A study on patient satisfaction in out patient department of secondary care hospital of Bhopal

Abstract: Background:  Patient satisfaction is as important as other clinical health measures and is a primary means of measuring the effectiveness of health care delivery. Patient-centered outcomes have taken central stage as the primary means of measuring the effectiveness of health care delivery. To evaluate the level of patient satisfaction with OPD services in terms of describing the experience of patients about medicine OPD services and accessibility to services among the patients who attended the medicine OPD of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
2
13
1
Order By: Relevance
“…Another study done at the OPD in Jaiprakash Hospital in Bhopal, India revealed that 80% (n=160) of patients were satisfied with the services delivered at the reception area (14). In contrast, less satisfaction of patients was seen with regards to registration services in the current study, possibly due to the overcrowding of the registration area.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Another study done at the OPD in Jaiprakash Hospital in Bhopal, India revealed that 80% (n=160) of patients were satisfied with the services delivered at the reception area (14). In contrast, less satisfaction of patients was seen with regards to registration services in the current study, possibly due to the overcrowding of the registration area.…”
Section: Discussioncontrasting
confidence: 79%
“…76% (n=152) respondents also agreed on the doctor's service (14). Another study on patient satisfaction with OPD services in Khmer-Soviet Friendship Hospital, Phnom Penh city, Cambodia reported that as much as 96.5% (n=193) of the patients were satisfied with regard to the cleanliness of OPD premises (5).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a study that poorly maintained toilet is one of the factors leading to patient's dissatisfaction from physical aspects of a hospital [39]. Furthermore, what were also found to be consistent with our study were the findings of Joshi S et al In their study the poor experience found was from the OPD doctors and about the diagnostic place [40]. Similarly, compatible with our findings was the study of V Kulkarni et al(2018) where poor satisfaction was related to cleanliness in toilets (56.01%) and this was further found to be statistically highly significant (P<0.0001) when compared with other areas in the hospital [41].…”
Section: Discussionsupporting
confidence: 93%
“…The factors associated with patient satisfaction include waiting time prior to doctor's consultation [12]. Respondents who reported ever having longer waiting time were three times and they are likely to report a low level of satisfaction on services received in outpatient department (OPD) of any tertiary health institution compared to those who said they had shorter waiting time [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The level of patient satisfaction is a major factor for measuring the QoC rendered by a health institution [12,13].…”
Section: Introductionmentioning
confidence: 99%